2004
DOI: 10.1021/tx0341862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Azaspiracids 2 and 3 on Intracellular cAMP, [Ca2+], and pH

Abstract: Azaspiracids (AZs) are a new group of phycotoxins discovered in the Ireland coast that includes the isolated analogues: AZ-1, AZ-2, AZ-3, AZ-4, and AZ-5 and the recently described AZ-6-11. Toxic episodes of AZs show gastrointestinal illness as in diarrhetic shellfish poisoning, but neurotoxic symptoms are also observed in a mouse bioassay. Despite their great importance in human health, so far, its mechanism of action is largely unknown. In this report, we present the first data of AZ-2 and AZ-3 effects on int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 51 publications
(60 reference statements)
1
39
0
Order By: Relevance
“…This was suspected early on by the Botana group when studying secondary messenger systems (28,29,38,41) and also reported more recently by the Murray group when they observed a discrepancy between the effects of AZA1 and fragments of AZA1 on cytotoxicity and spontaneous calcium ion oscillations (31). We have documented previously the total retraction of pseudopodia in T lymphocyte cells caused by AZA1 in a time-dependent manner that was specific to AZA1 but not elicited by a wide variety of other marine phycotoxins (24).…”
Section: Effects Of Aza Analogs Onsupporting
confidence: 59%
See 1 more Smart Citation
“…This was suspected early on by the Botana group when studying secondary messenger systems (28,29,38,41) and also reported more recently by the Murray group when they observed a discrepancy between the effects of AZA1 and fragments of AZA1 on cytotoxicity and spontaneous calcium ion oscillations (31). We have documented previously the total retraction of pseudopodia in T lymphocyte cells caused by AZA1 in a time-dependent manner that was specific to AZA1 but not elicited by a wide variety of other marine phycotoxins (24).…”
Section: Effects Of Aza Analogs Onsupporting
confidence: 59%
“…At relatively high concentrations (i.e., 50-1000 nM), AZA2, AZA3, AZA4, and AZA5 have been shown to have various effects on intracellular pH, cytosolic calcium, and cAMP in lymphocytes (29,41,42 (31). This study provided the first side-by-side evidence for potency differences among these regulated toxins.…”
Section: Acs Paragon Plus Environment Chemical Research Inmentioning
confidence: 69%
“…AZA‐1 induced an increase in the intracellular free Ca 2+ concentration in human lymphocytes and mouse primary cerebellar granule neurons [14,32]. AZA‐2 modulated the intracellular Ca 2+ concentration by enhancing the intracellular Ca 2+ rise induced by pharmacological means in lymphocytes, and AZA‐3 induced a Ca 2+ increase by itself, similarly to AZA‐1 [33]. AZAs also induced an increase in intracellular cAMP levels in lymphocytes [32,33].…”
Section: Other Aza‐induced In Vitro Effectsmentioning
confidence: 99%
“…11, 12 In vitro studies have shown the AZAs to be highly cytotoxic causing a variety of cytoskeletal effects 13-18 and stimulation of cAMP production and cytosolic calcium release. 19, 20 In spinal cord neurons, AZA1 was shown to inhibit bioelectrical activity through a mechanism that was independent of voltage-gated sodium (Na + ) or calcium (Ca 2+ ) current. 21 Recent findings suggest the AZAs cause apoptosis, 13, 22, 23 although this toxin class may have multiple molecular targets 13, 14 and also induce necrotic pathways concurrently.…”
Section: Introductionmentioning
confidence: 99%